A survey for prevention of black hole attacks in wireless mobile adhoc networks using trusted neighbor nodes - Araghi, Tanya Koohpayeh (2013)
Wireless mobile ad hoc networks can be regarded as a novel paradigm in wireless communication whereas wireless nodes act as either computers or routers. The transmission of information is performed via wireless links in which the radio frequencies are relayed to the outside of their radio range by their neighbor nodes, so in a MANET neighbor nodes play an important role in the transmission of information. This paper, categorized the solutions for prevention of black hole attacks based on the behavior of their neighbor nodes to find the attacker. Due to this classification in the proposed solutions we do not use any computation based on cryptographic or IDS based methods, instead we judge on malicious behavior just by getting the confirmation of the neighbor nodes to use the simplicity of these methods and avoid computational overheads.